PRISM (Pictorial Representation of Illness and Self-Measure) as Visual Tool to Support Oral Health Education Prior to Endoprosthetic Joint Replacement—A Novel Approach in Dentistry - Schmalz, Gerhard; Schmidt, Laura; Haak, Rainer; Büchi, Stefan; Goralski, Szymon; Roth, Andreas; Ziebolz, Dirk (Journal of clinical medicine, 2022)
Objective: This study aims to evaluate the application of Pictorial Representation of Illness and Self-Measure (PRISM) in educating patients regarding oral health before endoprosthesis (EP). Methods: The study consisted of two parts: (I) a cross-sectional study, where patients received a PRISM interview, oral health briefing and oral examinations (treatment need, oral focus). (II) In an observational part, patients were randomly assigned to either PRISM task (Test) or flyer-based verbal briefing (Control). Before and after the interviews, patients answered a questionnaire regarding importance of oral health for EP. Results: (I) 122 patients were included. The distance between subject (“myself”) and objects (oral health issues or EP) in the PRISM task were mainly not associated with age, gender, and oral conditions. In part (II), 80 patients (PRISM: n = 40, Control: n = 40) were included. After the interview, the values for perceived relationship between EP and teeth (p < 0.01), EP and gums (p < 0.01), and EP and dental consultations (p < 0.01) significantly increased in both groups. Both groups perceived a high benefit of the interview and felt well educated. Conclusions: PRISM has comparable positive effects like a flyer-based verbal briefing. PRISM as a novel visual tool can support the patient education regarding oral health before EP.